Digenic Variants in the TTN and TRAPPC11 Genes Co-segregating With a Limb-Girdle Muscular Dystrophy in a Han Chinese Family - Chen, Qian; Zheng, Wen; Xu, Hongbo; Yang, Yan; Song, Zhi; Yuan, Lamei; Deng, Hao (Frontiers in Neuroscience, 2021)
Limb-girdle muscular dystrophies (LGMD) are hereditary genetic disorders characterized by progressive muscle impairment which predominantly include proximal muscle weaknesses in the pelvic and shoulder girdles. This article describes an attempt to identify genetic cause(s) for a LGMD pedigree via a combination of whole exome sequencing and Sanger sequencing. Digenic variants, the titin gene (TTN) c.19481T>G (p.Leu6494Arg) and the trafficking protein particle complex 11 gene (TRAPPC11) c.3092C>G (p.Pro1031Arg), co-segregated with the disease phenotype in the family, suggesting their possible pathogenicity.